2014
DOI: 10.1002/poc.3320
|View full text |Cite
|
Sign up to set email alerts
|

Conformation/Tautomerization effect on the pKa values of lumazine and 6‐thienyllumazine

Abstract: Density functional theory p)] was used in combination with the conductor-like polarizable continuum model (CPCM) solvation model to investigate the relative stability and site-specific pK ij a values of neutral and ionized tautomers of lumazine (LM) and 6-thienylLM (TLM). Two types of populations should be taken into consideration when calculating the pK ij a , tautomers, and conformers. The major tautomer of neutral LM in aqueous solution is 13-LM (the 13 notation refers to the acidic protons being in positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…They found that the major tautomer of neutral lumazine in aqueous solution is the 1,3-dioxo form (see Scheme ) but 2% of the population is in the form of the 3,8-dioxo tautomer. The deprotonation of lumazine to form the anionic (A) form has an experimental p K a of about 8. According to the DFT calculations of ref , the anionic A form also consists of two major forms. The proton can reside on the nitrogen atom at position 1 (6%) or at position 3 (94%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the major tautomer of neutral lumazine in aqueous solution is the 1,3-dioxo form (see Scheme ) but 2% of the population is in the form of the 3,8-dioxo tautomer. The deprotonation of lumazine to form the anionic (A) form has an experimental p K a of about 8. According to the DFT calculations of ref , the anionic A form also consists of two major forms. The proton can reside on the nitrogen atom at position 1 (6%) or at position 3 (94%).…”
Section: Resultsmentioning
confidence: 99%
“…We assign this absorption band to the neutral form of lumazine that exhibits two protons. Recently, Afaneh and Schrekenbach 38 used DFT calculations to investigate the relative stability and site-specific pK a values of neutral, anionic, and dianionic tautomers of lumazine. They found that the major tautomer of neutral lumazine in aqueous solution is the 1,3-dioxo form (see Scheme 3) but 2% of the population is in the form of the 3,8-dioxo tautomer.…”
Section: ■ Experimental Resultsmentioning
confidence: 99%
“…53 The monohydroxy derivatives are less stable by about 14−26 kcal/ mol compared to this structure; whereas, the energy difference with the dihydroxy derivative is 20 and 22 kcal/mol in the gas and aqueous states, respectively. 53 Therefore, the ground state population of Lm is dominated by the dioxo structure, and we will confine our discussion of the spectral properties to this structure only. To understand the behavior of the absorption spectra for the complexes 2+ , we have carried out TDDFT calculations of Lm, TLm, and the complexes.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Various cations and anions in the structure of TLm may occur in various tautomeric forms because of protonation at the nitrogen atom sites and deprotonation at the oxo sites. Fortunately, Afaneh and Schreckenbach [30] computationally investigated the most stable prototropic structures of TLm in gas and aqueous phases at the ground state taken into consideration all possible tautomers and conformers, as illustrated in Chart 1. The authors concluded that insertion of thienyl group into the carbon atom at position 6 introduced two different conformers (cis and trans).…”
Section: Conformation and Tautomerization Effects On The Photoacid Behaviour Of 6-thienyl-substituted Lumazine Chromophore In Aqueous Solmentioning
confidence: 99%
“…The D form has an emission maximum at 435 nm. The most stable neutral and anionic tautomers and conformers, which were calculated in aqueous solution by Afaneh and Schreckenbach [30], were assumed to give the decay-associated spectra (DAS) amplitudes and the excited-state lifetime values in Table 1. Because strong acids are known to significantly decrease lifetime constants, the two conformers of the minor species 38-N (3.0 ns) were not resolved by our instrument at pH 2-4.…”
Section: Conformation and Tautomerization Effects On The Photoacid Behaviour Of 6-thienyl-substituted Lumazine Chromophore In Aqueous Solmentioning
confidence: 99%